2011
DOI: 10.1007/s10995-011-0848-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Factors Associated with the Risk of a Nicotine Exposed Pregnancy: Expanding the CHOICES Preconception Counseling Model to Tobacco

Abstract: The preconception counseling model tested in the CDC funded Project CHOICES efficacy trial to reduce the risk of an alcohol-exposed pregnancy (AEP) could be extended to smokers to prevent a nicotine-exposed pregnancy (NEP), when pharmacotherapy can be provided safely and disclosure of these risk behaviors is more likely. The CHOICES model, which incorporates motivational interviewing, encourages reduction of AEP risk by decreasing risky drinking or using effective contraception; in the efficacy trial, most wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Targeted preconception interventions have been found to be effective for other substance use among women. 127 By targeting AI/AN women before conception, this approach could have downstream effects on preventing tobacco use among AI/AN children. 1,128…”
Section: Gaps and Opportunities For Further Researchmentioning
confidence: 99%
“…Targeted preconception interventions have been found to be effective for other substance use among women. 127 By targeting AI/AN women before conception, this approach could have downstream effects on preventing tobacco use among AI/AN children. 1,128…”
Section: Gaps and Opportunities For Further Researchmentioning
confidence: 99%
“…MI is an effective technique to elicit change. The objective of this intervention, which has roots in cognitive-behavioral approaches, is to provide individuals with sufficient education and knowledge regarding the severity of preconception risk behaviors on future birth outcomes, with the hope that, as a result, individuals will become introspective and self-motivated to change (51,52,(64)(65)(66). SAMHSA offers online training to develop or enhance motivational interviewing skills, integrating the six elements of the FRAMES model into brief interventions, optimizing the motivation to change.…”
Section: Brief Interventionsmentioning
confidence: 99%
“…Although the CHOICES intervention is used primarily to reduce AEP, Parrish et al proposed expanding the CHOICES intervention to reduce nicotine-exposed pregnancy (NEP) and to promote the smoking cessation intervention for women at risk (66). They found that the co-occurrence of AEP and NEP risks was more prevalent than the AEP risk alone (16%).…”
Section: Brief Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…100 Another program was effective for preconception smoking cessation counseling. 101 Approximately 45% of women in the general population stop smoking on finding out they are pregnant. 96 An equivalent figure is unknown for Indigenous women.…”
Section: Cessation Before Conceptionmentioning
confidence: 99%